2022
DOI: 10.1093/jimb/kuac012
|View full text |Cite
|
Sign up to set email alerts
|

Electroactive biofilms: how microbial electron transfer enables bioelectrochemical applications

Abstract: Microbial biofilms are ubiquitous. In marine and freshwater ecosystems, microbe-mineral interactions sustain biogeochemical cycles, while biofilms found on plants and animals can range from pathogens to commensals. Moreover, biofouling and biocorrosion represent significant challenges to industry. Bioprocessing is an opportunity to take advantage of biofilms and harness their utility as chassis for biocommodity production. Electrochemical bioreactors have numerous potential applications, including wastewater t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 142 publications
0
4
0
Order By: Relevance
“…It is important to note that the normal operational range of the BES observed in this study does not necessarily indicate a universal measurement range for BESs applied in WRRFs. Given the dynamic nature of anodic electroactive biofilm formation under different environments and operating conditions, it would not be possible to expect identical signal baselines from BESs installed in different unit processes and locations; this is due to differences in the microbial composition of anodic biofilms, biofilm thickness, and mass transfer considerations. It has also been reported that temperature variations can alter the BES signal baseline; therefore, it would not be possible to explicitly determine the measurement range of BESs applied in full-scale industrial environments and under uncontrolled conditions with a high degree of confidence.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that the normal operational range of the BES observed in this study does not necessarily indicate a universal measurement range for BESs applied in WRRFs. Given the dynamic nature of anodic electroactive biofilm formation under different environments and operating conditions, it would not be possible to expect identical signal baselines from BESs installed in different unit processes and locations; this is due to differences in the microbial composition of anodic biofilms, biofilm thickness, and mass transfer considerations. It has also been reported that temperature variations can alter the BES signal baseline; therefore, it would not be possible to explicitly determine the measurement range of BESs applied in full-scale industrial environments and under uncontrolled conditions with a high degree of confidence.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors studied the mechanism involved in electron transfer between the electrode and electroactive PPB, such as Rhodopseudomonas palustris TIE-1. These studies reveal that R. palustris TIE-1 encodes three protein types to mediate the external electron transfer: multiheme cytochrome c, an outer membrane porin, and a periplasmic high-potential iron-sulfur protein 22,[33][34][35] .…”
Section: Discussionmentioning
confidence: 96%
“…Subsequently, the oxidized electron shuttle diffuses back and gets recharged by electrons to form reduced electron shuttle, which participates in the next cycle of electron transport. This shuttling of the electron shuttle enables inward electron transfer and NAD(P)H regeneration (Conners et al, 2022; Malapit et al, 2022). Thus, MES system can achieve direct regeneration of intracellular reducing power (Mayr et al, 2019; Pandit & Mahadevan, 2011; Wang et al, 2015, 2017), bypassing the laborious genetic modification forementioned.…”
Section: Introductionmentioning
confidence: 99%